Application of Tuned Liquid Damper to Control the Structural Vibration: Review Paper: Advances and Applicability of Tuned Liquid Dampers in Structural Response Control (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Response controls of structures with different forms of dampers have been a core area of study which was adopted to mitigate various natural hazards like earthquake and wind. Active, passive and hybrid dampers of different forms are generally used in structures to make structures more flexible. Tuned liquid damper or TLD has been common form of damper as a response controller and has undergone different modifications in its functionality and installation to decrease the structural vibration during an earthquake. Till now several successful applications validate with the numerical, experimental and analytical investigation has been presented on TLD. For the experimental study shake table is used to find out the response of the structure. This paper presents a detailed study carried out to investigate the advances in tuned liquid dampers and its applicability in the structure. Also gives the report on various aspects of the tuned liquid damper.